2021
DOI: 10.1038/s41598-021-03549-5
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial inequality, active lifestyle and chronic health conditions: a cross-sectional National Health Survey 2013 in Brazil

Abstract: This study estimated the biopsychosocial factors related to active physical behavior in the Brazilian population with and without chronic non-transmissible disease (NCD). Cross-sectional study of the National Health Survey (NHS) in Brazil, with 60,202 individuals in 2013. Participants were randomly selected by complex sampling. The outcome was physically active behavior measured by performing a minimum of 150 min of physical exercise per week. The independent variables were social and psychological characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 43 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…Regarding being male and having a higher chance of being physically active in the group without NCD, similar results were found by Guedes et al (2021) [20]. The literature has shown gender inequality in physical activity [18,28].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Regarding being male and having a higher chance of being physically active in the group without NCD, similar results were found by Guedes et al (2021) [20]. The literature has shown gender inequality in physical activity [18,28].…”
Section: Discussionsupporting
confidence: 83%
“…Having a high level of education and a high per capita income are significant factors for engaging in physical activity in leisure time. Guedes et al (2021) [20] showed similar results, making it possible to analyze that the realization and encouragement of leisure-time physical activities have a higher frequency among people with higher education levels, which generates a better understanding of the importance of staying physically active, such as the necessary health care, leading these individuals to use the health system more frequently [36].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations